ANALISIS YURIDIS SURAT KETERANGAN GANTI RUGI SEBAGAI BUKTI PENGUASAAN HAK ATAS TANAH - Zelot Agripa Hutagalung (Ensiklopedia of Journal, 2022)
The negative principle adopted in the land registration system in Indonesia causes the validity of the certificate to be challenged if there is another party who can prove that the party is the owner. One of the proofs of ownership of land rights that challenge the validity of the certificate is the Certificate of Compensation (SKGR) which is considered as proof of land tenure that has not been certified, especially in Pekanbaru City, Riau Province. The purpose of this study is to obtain an overview of legal arrangements and implementation, constraint factors and solutions in the form of a Certificate of Compensation (SKGR) as proof of control of land rights in the city of Pekanbaru. The research method used in this research is normative juridical, which is based on positive legal rules or norms through the relevant legislation. The specification of the research used is descriptive analysis, which is carried out by analyzing and describing completely and thoroughly the secondary data sources studied in order to obtain a comprehensive and systematic picture of the legal position and strength of the Certificate of Compensation made before the Camat in Pekanbaru City is reviewed from Government Regulation Number 18 of 2021. From the research conducted, the results obtained are: First, the position of written evidence in the form of a Certificate of Compensation in Riau Province is evidence of the transfer of physical control over a plot of land which can then be used as a guide in the process land registration. Second, the strength of proof of the Indemnity Certificate refers to Article 96 of Government Regulation Number 18 of 2021 which for old rights and for the purposes of land registration can be proven through written evidence and witness statements that can be guaranteed the truth and if not fully available tools Evidence, can be proven by physical control over a plot of land in good faith for 20 consecutive years accompanied by statements of at least 2 witnesses confirmed by the Village Head.